Preparation of ammonium-modified cassava waste-derived biochar and its evaluation for synergistic adsorption of ternary antibiotics from aqueous solution. (15th November 2021) - Luo, Jiwei; Li, Xue; Ge, Chengjun; Müller, Karin; Yu, Huamei; Deng, Hui; Shaheen, Sabry M.; Tsang, Daniel C.W.; Bolan, Nanthi S.; Rinklebe, Jörg; Ok, Yong Sik; Gao, Bin; et al.
Abstract: Mono- and co-sorption of the three antibiotics i.e., norfloxacin (NOR), sulfamerazine (SMR) and oxytetracycline (OTC), to raw and NH4 + -modified cassava waste biochar added to aqueous solutions were investigated. The NH4 + -modified biochar showed higher sorption affinity for both NOR and SMR than the raw biochar, while the raw biochar showed higher sorption affinity for OTC than the modified biochar. The highest sorption to both biochars in both the mono- and competitive sorption systems was found for OTC followed by NOR and SMR. Sorption equilibrium in all systems analyzed was reached within 15 h. Electrostatic interactions among the ionic antibiotics in the multicomponent solution increased NOR and SMR sorption to both biochars. Antibiotics' mono- and co-sorption to biochars decreased with increasing solution pH. The co-sorption of NOR and SMR to the two biochars was regulated by π-π electron-donor-acceptor (EDA) interactions; besides, electrostatic interactions and Hydrogen (H-) bonding played an important part. Cation bridging might have been a potential mechanism to contribute to SMR sorption to the raw biochar, and OTC sorption to the NH4 + -modified biochar. These observations will improve our understanding of the simultaneous removal of multiple antibiotics from water or wastewater. Graphical abstract: Image 1 Highlights: NH4 + -modification of biochar enhanced the sorption of antibiotics from solution. Sorption efficiency for antibiotics was higher in ternary than mono-solute systems. Sorption capacity was found to be oxytetracycline > norfloxacin > sulfamerazine. π-π EDA, electrostatic interactions and H-bonds were the major sorption mechanisms.